The Madhhab-Oriented Paradigm in Fiqh Instruction at Salafiyah-Style Islamic Boarding Schools in Mandailing Natal Regency and Its Relevance to the Reform of Family Law in Indonesia - Muhammad Fadhlan Is; Dede Hafirman Said (Kartika: Jurnal Studi Keislaman, 2025)
Mandailing Natal Regency is recognized as a "santri city" in Indonesia. However, in practice, violations of family law provisions persist within the community. Furthermore, there is widespread skepticism regarding the authority of renewed Islamic Law in Indonesia compared to the classical fiqh rulings traditionally taught in Islamic boarding schools (pesantren). This study employs a descriptive qualitative approach through field research. Primary data were collected via direct interviews and questionnaires. The research focuses on analyzing fiqh instruction in Salafiyah-style Pesantren, examining the madhhab (school of thought) paradigms of teachers and students, and assessing their responses to the reforms in Indonesian Islamic Family Law. The findings conclude that the teaching method in Salafiyah-style pesantren in Mandailing Natal utilizes a classical system centered on the Shafi’iyyah madhhab-oriented kitab kuning (classical texts). The adherence to a madhhab among teachers and students is notably high. In contrast, the response to reforms in Islamic Family Law is relatively low. This is attributed to the strong consistency in madhhab adherence within the Salafiyah pesantren environment, resulting in a limited relevance and responsiveness to such legal reforms.